A Study on The Implementation of English Interactive Radio Instruction (IRI) in Selected Government Primary Schools in Addis Ababa - Alaro, Meseret (Addis Ababa University, 2007)
As its central objective, this study attempts to assess the implementation of English Interactive Radio Instruction (IRI) in selected government primary schools in Addis Ababa. In line with that, the researcher has framed specific questions that address issues related to classroom management, training given to the teachers, links among different stakeholders and the suitability and clarity of the program. Students and teachers of Grade Three from Biherawi Betemengist, Edget Besira , Karalo , Lafto and Salayish Primary Schools are participants of this study .To undertake the study descriptive research design is used . Accordingly, data that is pertinent to the study is collected using different tools such as questionnaire, observation, focus group discussion, interview and document analysis. The findings of the study reveal that the implementation of the program seems to face grave challenges. These mainly emanate from loose link among stakeholders, failure of supplying basic facilities needed to promote the fruitfulness of the program and failure to arrange suitable conditions for the broadcast. Moreover, based on the opinion of the participants, results of the study highlight that in some cases contents of the program is not suitable compared to the students language proficiency .It is also noticed from the findings of the study that classroom practice is not effectively carried out as per the very goal of the program. Despite that, both students and teachers forward positive comments about the utilization of the program for the teaching of English. Based on the findings recommendations for better service and suggestions for further studies are given.

Small-group problem-based learning as a complex adaptive system - Mennin, Stewart (Teaching and Teacher Education, 2007)
Small-group problem-based learning (PBL) is widely embraced as a method of study in health professions schools and at many different levels of education. Complexity science provides a different lens with which to view and understand the application of this method. It presents new concepts and vocabulary that may be unfamiliar to practitioners of small-group PBL and other educational methods. This article looks at small-group PBL from the perspective of complex adaptive systems (CAS). It begins with a brief review of the current understanding and practice of PBL. Next some of the characteristics of CAS are reviewed using examples from small-group PBL to illustrate how these characteristics are expressed in that context. The principles and the educational theory in which small-group PBL are embedded are related to CAS. Implications for health professions education are discussed.

Integrating technology into K-12 teaching and learning: current knowledge gaps and recommendations for future research - Hew, Khe Foon; Brush, Thomas (Educational Technology Research and Development, 2007)
Although research studies in education show that use of technology can help student learning, its use is generally affected by certain barriers. In this paper, we first identify the general barriers typically faced by K-12 schools, both in the United States as well as other countries, when integrating technology into the curriculum for instructional purposes, namely: (a) resources, (b) institution, (c) subject culture, (d) attitudes and beliefs, (e) knowledge and skills, and (f) assessment. We then describe the strategies to overcome such barriers: (a) having a shared vision and technology integration plan, (b) overcoming the scarcity of resources, (c) changing attitudes and beliefs, (d) conducting professional development, and (e) reconsidering assessments. Finally, we identify several current knowledge gaps pertaining to the barriers and strategies of technology integration, and offer pertinent recommendations for future research.

Emerging Technologies: An Overview of Practices in Distance Education - Hussain, Irshad (Journal on School Educational Technology, 2007)
In contemporary society, information technologies and communication technologies (ICTs) are playing crucial role in dissemination of knowledge and information the world over. Universities/ higher education institutions, particularly distance education universities in developed countries are making best use of these technologies for effective and interactive teaching learning process. Developing countries are also trying to adopt the model of developed countries according to their resources and circumstances. Distance education universities in developed countries like United States of America and United Kingdom are using advanced (emerging) technologies such as computers, Internet (World Wide Web) satellite communication, teleconferencing (videoconferencing and audio conferencing) and virtual reality in education and training. In developing countries like India, Pakistan and Thailand, distance education universities are using Radio, Television and Internet for teaching learning purpose and students support services. They are using computers mostly for office work. They are trying to adopt advanced technologies like developed countries but they have some limitations of resources (human & material resources). In future it is hoped that developing countries will also be using emerging technologies for teaching learning purpose.
Keywords: Case Studies; Computer Mediated Communication; Distance Education; Educational Development; Educational Practices; Educational Technology; Educational Television; Foreign Countries; Influence of Technology; Information Networks; Online Systems; Open Universities; Technological Advancement; Technology Integration; Technology Uses in Education; Telecommunications; Virtual Universities

Teacher Motivation in Sub-Saharan Africa and South Asia - Bennell, Paul; Akyeampong, Kwame (Department for International Development: Educational Papers, 2007)
This is one of a series of Education Papers issued by the Central Research Department of the Department For International Development. Each paper represents a study or piece of commissioned research on some aspect of education and training in developing countries. Most of the studies were undertaken in order to provide informed judgements from which policy decisions could be drawn, but in each case it has become apparent that the material produced would be of interest to a wider audience, particularly those whose work focuses on developing countries.This report synthesises the main findings and recommendations of an international research project on teacher motivation and incentives in sub-Sahara Africa and South Asia. The study has addressed the following four main questions: • To what extent is there a problem of poor motivation among teachers in sub-Saharan Africa and South Asia? Does this amount to a ‘crisis’, as has been suggested by some observers? • If so, what are the main reasons for poor teacher motivation? • How do poor motivation and incentives affect teacher performance and the overall effectiveness of national education systems? • What should be done to ensure that teachers are adequately motivated?
Keywords: C:sub-Saharan Africa and South Asia; ⛔ No DOI found

Investigating educational change: The Aga Khan University Institute for educational development teacher education for school improvement model - Khamis, Anil; Sammons, Pamela (International Journal of Educational Development, 2007)
This article continues the analyses of the impact of an innovative teacher education programme aimed at school improvement in a developing country context (A. Khamis, P. Sammons, 2004. The development of a cadre of teacher educators: some lessons from Pakistan. International Journal of Educational Development, 24(3), 255–268). Building on recent publications that have analysed outcomes of the teacher education programme and how the cadre of teacher educators has worked to initiate improvement in schools in Pakistan. The article considers the ‘teacher education for school improvement model’ based on findings from the case studies of nine co-operating school. Lessons are presented to further inform the development of teacher education programmes and the measurement of effectiveness of such programmes in developing country contexts. The article further considers relevant international research on educational change and reform to draw further lessons. These lessons include the need to pay greater attention to the cultural contexts and milieu in Pakistan, and the need to create models of school improvement and teacher education that originate within developing country contexts rather than the adaptation of European/North American models that are based on sources of data in those contexts. The article concludes by arguing for the need to develop better theoretical understandings from the current innovations underway and placing the onus on intervening agencies to better inform educational change strategies promoted in developing country contexts.
Keywords: Developing countries; Educational change; Innovation; Pakistan; School improvement; Teacher education